Degradable high-elasticity TPU composite material and preparation method thereof
By combining modified nanocellulose and polylactic acid with TPU matrix, the problems of non-degradability, poor compatibility and weak thermal stability of traditional TPU materials are solved, achieving high elasticity and degradability, which is suitable for automotive parts and medical consumables.
Patent Information
- Application Number
- CN202610210915.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-13
- Publication Date
- 2026-03-20
AI Technical Summary
Traditional TPU materials are non-degradable, have poor compatibility, insufficient mechanical properties, weak thermal stability, and complex and costly manufacturing processes, making it difficult to meet the needs of environmental protection and high-end applications.
Modified nanocellulose and modified polylactic acid are combined with TPU matrix, and the compatibility and dispersibility are improved through multi-step modification treatment. The elasticity and thermal stability of the material are optimized by combining components such as polybutylene adipate diol and polycaprolactone. The material is then mass-produced using conventional equipment and processes.
It achieves a balance between biodegradability and high elasticity, improves the material's compatibility, mechanical properties and thermal stability, reduces production costs, broadens application scenarios, and is suitable for fields such as automotive parts and medical consumables.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of biodegradable polymer composite materials technology, specifically to a biodegradable, highly elastic TPU composite material and its preparation method. Background Technology
[0002] Thermoplastic polyurethane (TPU), a polymer material combining the elasticity of rubber and the processing properties of plastics, has been widely used in various fields such as automotive parts, medical consumables, packaging materials, and sporting goods due to its excellent tensile strength, abrasion resistance, and fatigue resistance. However, traditional TPU materials are mostly made from non-degradable petroleum-based raw materials, which are difficult to degrade in the natural environment after use. Long-term accumulation can easily cause serious white pollution, which contradicts the current global advocacy of low-carbon, environmentally friendly, and sustainable development concepts. Its lack of environmental friendliness is becoming increasingly prominent.
[0003] To address the environmental shortcomings of traditional TPU, researchers have been exploring the development of biodegradable TPU composites. By introducing biodegradable polyester components such as polylactic acid (PLA) and polycaprolactone (PCL), biodegradable properties are endowed into the materials. However, the development of biodegradable TPU still faces many bottlenecks in the current technology: on the one hand, biodegradable polyesters such as PLA have poor compatibility with the TPU matrix, and direct blending can easily lead to uneven internal structure of the material and a significant decrease in mechanical properties, especially elasticity and toughness. On the other hand, although inorganic reinforcing fillers such as nanocellulose can improve the strength of the material, unmodified fillers are prone to agglomeration in the polymer matrix, which cannot fully exert the reinforcing effect and may also disrupt the continuity of material degradation.
[0004] Meanwhile, existing biodegradable TPU materials generally suffer from insufficient thermal stability and poor anti-aging properties, making them prone to degradation and failure during high-temperature processing or long-term use, thus limiting their application in high-end fields. In addition, some preparation processes are complex, require harsh reaction conditions, or rely on expensive specialized equipment and reagents, resulting in high production costs and making it difficult to achieve large-scale mass production.
[0005] Therefore, developing a TPU composite material that combines excellent biodegradability, high elasticity, good mechanical properties and thermal stability, with a controllable preparation process and reasonable cost, can not only break through existing technological bottlenecks, but also meet environmental protection policy requirements and actual market demands, which is of great significance for promoting the green transformation of the polymer materials industry. Summary of the Invention
[0006] To address the shortcomings of existing technologies, this invention provides a biodegradable and highly elastic TPU composite material and its preparation method, solving the problems of traditional TPU being non-degradable, biodegradable TPU having poor compatibility, insufficient mechanical properties, and weak thermal stability.
[0007] To achieve the above objectives, the present invention provides the following technical solution: A biodegradable and highly elastic TPU composite material comprises the following raw materials in parts by weight: 35-45 parts polybutylene adipate diol, 12-18 parts 2,4-toluene diisocyanate, 3-8 parts 1,4-butanediol, 2-6 parts modified nanocellulose, 5-12 parts modified polylactic acid, 8-15 parts polycaprolactone, 0.2-0.5 parts antioxidant 1010, and 1-4 parts epoxidized soybean oil.
[0008] Furthermore, the polybutylene adipate diol has a number-average molecular weight of 2000-3000, ensuring suitable reactivity with isocyanate, while also imparting good elastic recovery and toughness to the material, avoiding insufficient mechanical properties caused by poor processing flowability due to excessively high molecular weight or insufficiently low molecular weight.
[0009] Furthermore, the polycaprolactone has a number-average molecular weight of 1500-2500, a melt index of 5-12 g / 10 min at 190℃ / 2.16 kg, and a terminal hydroxyl content of ≥98%. The high terminal hydroxyl content enhances the chemical bonding force with the TPU matrix, improves compatibility and degradation continuity, and simultaneously optimizes the material's elasticity and biodegradability in synergistic effect with polybutylene adipate diol.
[0010] Furthermore, the modified nanocellulose is prepared using the following specific steps: A1. Take nanocellulose, add deionized water, and ultrasonically disperse for 40 min to obtain a nanocellulose dispersion. Place it in a three-necked flask, heat to 60-70℃, and stir at 200-300 r / min. Slowly add silane coupling agent KH-560 to the flask, and simultaneously add 15% sodium carbonate solution in 3 portions. After the addition is complete, keep the reaction at the temperature for 5-7 h. Then add bisphenol F diglycidyl ether and continue to keep the reaction at the temperature for 3-4 h. After the reaction is complete, adjust the pH of the system to 6.5-7.5 with 5% acetic acid solution, vacuum filter, wash the filter cake 3 times with deionized water, and dry it in a vacuum drying oven at 70℃ for 12 h to obtain the first modified nanocellulose. By introducing organic functional groups through silane coupling agent, combined with crosslinking of bisphenol F diglycidyl ether and pH adjustment, the compatibility of nanocellulose with the organic matrix is improved, the dispersibility is initially improved, and the foundation for subsequent modification is laid.
[0011] A2. Take the first modified nanocellulose, add N,N-dimethylacetamide, ultrasonically disperse for 30 min, heat to 85-95℃, and stir at 250-350 r / min; add polymethyl methacrylate microspheres to the system, stir and disperse for 20 min, then slowly add hexamethylene diisocyanate, and keep the reaction at this temperature for 4-6 h; after the reaction is complete, cool the system to room temperature, vacuum filter, soak the filter cake in acetone for 8-12 h, then wash twice with acetone and once with deionized water, and dry in a vacuum drying oven at 75℃ for 10 h to obtain the second modified nanocellulose; introduce polymethyl methacrylate microspheres and hexamethylene diisocyanate crosslinking, and purify with solvent washing to further optimize the dispersion stability of nanocellulose, avoid agglomeration, and strengthen the interfacial bonding with the TPU matrix.
[0012] A3. Take the second modified nanocellulose, add 0.1 mol / L phosphate buffer (pH=7.2), and sonicate for 15 min. Then add glucose oxidase and stir at 4-8℃ for 12-16 h. Add 25% glutaraldehyde aqueous solution to the system and stir at room temperature for 2-3 h. Then add glycine and stir at 25℃ for 30 min to quench the aldehyde groups. After the reaction, vacuum filter the mixture. Wash the filter cake with 50℃ deionized water until the filtrate is free of aldehydes when tested with 2,4-dinitrophenylhydrazine test paper. Then dry the filter cake in a 70℃ vacuum drying oven for 8 h to obtain modified nanocellulose. Enzymatic oxidation to introduce aldehyde groups, glutaraldehyde crosslinking, and aldehyde group quenching treatment improve the biocompatibility and degradation coordination of nanocellulose, ultimately achieving the dual effect of enhancing the mechanical properties of the material and ensuring continuous degradation.
[0013] Furthermore, the ratio of nanocellulose, deionized water, silane coupling agent KH-560, sodium carbonate solution, and bisphenol F diglycidyl ether in A1 is 10g:450-550mL:18-25mL:12-18g:8-12g; the epoxy value of the bisphenol F diglycidyl ether is 0.55-0.60mol / 100g.
[0014] Furthermore, the ratio of the first modified nanocellulose, N,N-dimethylacetamide, polymethyl methacrylate, and hexamethylene diisocyanate in A2 is 8g:300-400mL:20-30g:5-8g; and the polymethyl methacrylate microspheres have a particle size of 200-500nm.
[0015] Furthermore, the ratio of the amount of the second modified nanocellulose, phosphate buffer, glucose oxidase, glutaraldehyde aqueous solution, and glycine in A3 is 6g: 250-350mL: 10-15g: 6-10g: 1.2-2.0g.
[0016] Furthermore, the modified polylactic acid is prepared using the following specific steps: B1. Take polylactic acid, add chloroform, place in a three-necked flask, heat to 45-55℃, stir at 150-200 r / min until polylactic acid is completely dissolved, add polypropylene glycol diacrylate, stir and disperse for 10 min, then add 2,2-dimethoxy-2-phenylacetophenone, turn on ultraviolet light irradiation, wavelength 365nm, power 300W, irradiation distance 10-15cm, react for 3-5 h; after the reaction is complete, pour the system into anhydrous ethanol to precipitate, let stand for 3-4 h, then vacuum filter, wash the filter cake 2-3 times with anhydrous ethanol, place in a 55℃ vacuum drying oven and dry for 12-16 h to obtain the first modified polylactic acid; by initiating crosslinking of polypropylene glycol diacrylate with ultraviolet light, combined with precipitation purification, the brittleness of polylactic acid is improved, its flexibility and thermal stability are enhanced, and its inherent defects are solved.
[0017] B2. Take the first-modified polylactic acid and add it to the feed inlet of a twin-screw extruder. Set the temperatures of each zone of the extruder as follows: Zone 1 165-175℃, Zone 2 175-185℃, Zone 3 180-185℃, Die head 175-180℃, and screw speed 110-130 r / min to melt and plasticize it. The melt residence time is 2-3 min. Add adipate dihydrazide and tributyl citrate at a uniform speed through the side feed port. The reaction residence time is 3-5 min. After cooling the extrudate to room temperature with water, granulate it through a pelletizer to obtain second-modified polylactic acid granules with a particle size of 2-3 mm. After being melted and plasticized by twin-screw extrusion, the combined effect of chain extender and plasticizer improves the processing fluidity and compatibility of polylactic acid, making it easier to compound with other components in the future.
[0018] B3. Take the second batch of modified polylactic acid granules and add them to a mixer. Set the mixing temperature to 175-185℃ and the rotor speed to 70-90 r / min. After melting for 5-8 minutes, add polyetheramine D230 and maleic anhydride-grafted polyolefin, and continue mixing for 10-15 minutes. Remove the mixed product and place it on a flat vulcanizing machine for sheeting. Set the temperature to 180-190℃, the pressure to 10-15 MPa, and the time to 3-5 minutes. After cooling to room temperature, pulverize and pass through an 80-mesh sieve to obtain modified polylactic acid. Through mixing and the action of interface modifiers, the compatibility between polylactic acid and the TPU matrix is further optimized, synergistically improving the material's mechanical properties and elastic recovery rate.
[0019] Furthermore, the ratio of polylactic acid, chloroform, polypropylene glycol diacrylate, and 2,2-dimethoxy-2-phenylacetophenone in B1 is 20g: 400-500mL: 15-22g: 0.8-1.5g.
[0020] Furthermore, the ratio of the first modified polylactic acid, adipic acid dihydrazide, and tributyl citrate in B2 is 15g:12-18g:5-9g.
[0021] Furthermore, the ratio of the second modified polylactic acid particles, polyetheramine D230, and maleic anhydride grafted polyolefin in B3 is 12g:8-14g:2-5g.
[0022] A method for preparing a biodegradable, highly elastic TPU composite material, specifically comprising the following steps: S1. Place polybutylene adipate diol in a vacuum drying oven at 100-110℃ and dry for 6 hours; place modified nanocellulose, modified polylactic acid, and polycaprolactone in a vacuum drying oven at 80-90℃ and dry for 10 hours respectively; place antioxidant 1010, epoxidized soybean oil, and 1,4-butanediol in a dry, sealed container for later use. S2. Add 35-45 parts of pretreated polybutylene adipate diol to a four-necked flask, heat to 80-90℃, stir at 150-200 r / min, and purge with high-purity nitrogen gas at a flow rate of 20-30 mL / min. After the temperature stabilizes at 85-90℃, slowly add 12-18 parts of 2,4-toluene diisocyanate. After the addition is complete, maintain the temperature at 85-95℃ for 2-3 hours to obtain the TPU prepolymer. S3. Add 5-12 parts of pretreated modified polylactic acid and 8-15 parts of polycaprolactone to the above TPU prepolymer, heat to 95-105℃, increase the stirring speed to 250-300 r / min, and maintain the temperature for 1-1.5 h to form a preliminary composite system; then add 0.2-0.5 parts of antioxidant 1010 and 1-4 parts of epoxidized soybean oil, maintain the temperature at 95-105℃, and continue stirring for 30-40 min; then slowly add 2-6 parts of pretreated modified nanocellulose. Increase the stirring speed to 350-400 r / min, maintain the temperature at 95-105℃ for 1.5-2 h to form a uniform and stable composite system; finally, add 3-8 parts of 1,4-butanediol, raise the temperature to 105-115℃, and adjust the stirring speed to 200-250 r / min to carry out the chain extension reaction; continuously monitor the reaction process, and when the viscosity reaches 8000-12000 mPa·s and remains stable for 30 min, the chain extension reaction is complete, and a high-viscosity TPU composite melt is obtained; S4. Pour the extended TPU composite melt into a mold preheated to 120-130℃. Place the mold on a flat vulcanizing machine for compression molding. Set the molding pressure to 15-20MPa and the temperature to 125-135℃, and maintain the temperature and pressure for 30-40 minutes. After compression molding, turn off the heating device of the flat vulcanizing machine and allow the mold and the product to cool naturally to room temperature. After cooling, demold to obtain the composite material blank. Place the composite material blank in a vacuum drying oven at 80-90℃ and dry for 10 hours to obtain a biodegradable high-elasticity TPU composite material.
[0023] This invention provides a biodegradable, highly elastic TPU composite material and its preparation method, which has the following beneficial effects: 1. The TPU composite material prepared by this invention achieves a synergistic balance between degradability and high elasticity, effectively overcoming the technical bottleneck of traditional materials that struggle to simultaneously achieve environmental and performance benefits. Through multi-step targeted modification of nanocellulose and polylactic acid, the compatibility between the degradable components and the TPU matrix is significantly improved, avoiding phase separation problems that easily occur in blended systems. This allows the material to continuously and stably degrade in the natural environment, reducing white pollution. Simultaneously, the modified reinforcing components form a stable network structure with the matrix. Combined with a reasonable ratio of elastic components such as polybutylene adipate diol and polycaprolactone, the material possesses excellent elastic recovery properties and toughness, meeting the elasticity requirements of multiple fields such as automotive parts and medical consumables, achieving the dual value of environmental protection and practicality.
[0024] 2. The TPU composite material of this invention possesses balanced and excellent comprehensive mechanical properties, solving the defects of insufficient mechanical strength and brittleness in existing biodegradable TPUs. Modified nanocellulose, after multiple treatments including silane coupling agents and bisphenol F diglycidyl ether, exhibits significantly improved dispersibility, forming a uniform reinforcing skeleton in the composite material, effectively transferring stress, and significantly improving the tensile strength and impact resistance of the material. Meanwhile, modified polylactic acid, optimized through processes such as ultraviolet crosslinking and melt blending, has its own brittleness improved, and works synergistically with the TPU matrix to further enhance the mechanical stability of the material. Furthermore, the rational combination of antioxidant 1010 and epoxidized soybean oil not only enhances the material's anti-aging ability but also regulates the interfacial bonding state of the system, enabling the material to maintain stable mechanical properties during long-term use and broadening its application scenarios in high-end manufacturing.
[0025] 3. The preparation process of this invention is scientifically controllable, highly compatible, suitable for large-scale mass production, and has a competitive production cost advantage. Throughout the entire preparation process, parameters such as temperature, rotation speed, and reaction time in each stage, including raw material pretreatment, prepolymerization reaction, composite system construction, and compression molding, are precisely optimized. It eliminates the need for expensive specialized equipment; conventional polymer processing equipment can meet production requirements. Furthermore, the preparation processes for modified nanocellulose and modified polylactic acid are mature, the raw materials are readily available, and the dosage ratios are reasonable, avoiding the problem of excessively high production costs due to raw material scarcity or complex processes. In addition, the vacuum drying, nitrogen protection, and stepwise feeding operations employed in the process effectively reduce side reactions, improve product yield and stability, and provide favorable conditions for the industrial production and market promotion of the materials. Detailed Implementation
[0026] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0027] Example 1: Preparation of a biodegradable, highly elastic TPU composite material. The specific preparation steps are as follows: S1. Place polybutylene adipate diol in a vacuum drying oven at 100℃ and dry for 6 hours; place modified nanocellulose, modified polylactic acid, and polycaprolactone in a vacuum drying oven at 80℃ and dry for 10 hours respectively; place antioxidant 1010, epoxidized soybean oil, and 1,4-butanediol in a dry sealed container for later use. S2. Add 35 parts of pretreated polybutylene adipate diol to a four-necked flask, heat to 80℃, stir at 150 r / min, and purge with high-purity nitrogen gas at a flow rate of 20 mL / min. After the temperature stabilizes at 85℃, slowly add 12 parts of 2,4-toluene diisocyanate. After the addition is complete, maintain the temperature at 85℃ for 2 hours to obtain the TPU prepolymer. S3. Add 5 parts of pretreated modified polylactic acid and 8 parts of polycaprolactone to the above TPU prepolymer, heat to 95℃, increase the stirring speed to 250 r / min, and keep the reaction at this temperature for 1 h to form a preliminary composite system; then add 0.2 parts of antioxidant 1010 and 1 part of epoxidized soybean oil, keep the temperature at 95℃, and continue stirring for 30 min; then slowly add 2 parts of pretreated modified nanocellulose, increase the stirring speed to 350 r / min, and keep the temperature at 95℃ for 1.5 h to form a uniform and stable composite system; finally add 3 parts of 1,4-butanediol, heat to 105℃, and adjust the stirring speed to 200 r / min to carry out the chain extension reaction; continuously monitor the reaction process, and when the viscosity reaches 8000 mPa·s and stabilizes for 30 min, the chain extension reaction is complete, and a high-viscosity TPU composite melt is obtained; S4. Pour the extended TPU composite melt into a mold preheated to 120°C. Place the mold on a flat vulcanizing machine for compression molding. Set the molding pressure to 15MPa and the temperature to 125°C. Hold the temperature and pressure for 30 minutes. After compression molding, turn off the heating device of the flat vulcanizing machine and allow the mold and the product to cool naturally to room temperature. After cooling, demold to obtain the composite material blank. Place the composite material blank in an 80°C vacuum drying oven and dry for 10 hours to obtain a biodegradable high-elasticity TPU composite material.
[0028] Example 2: Preparation of a biodegradable, highly elastic TPU composite material. The specific preparation steps are as follows: S1. Place polybutylene adipate diol in a vacuum drying oven at 110℃ and dry for 6 hours; place modified nanocellulose, modified polylactic acid, and polycaprolactone in a vacuum drying oven at 90℃ and dry for 10 hours respectively; place antioxidant 1010, epoxidized soybean oil, and 1,4-butanediol in a dry sealed container for later use. S2. Add 45 parts of pretreated polybutylene adipate diol to a four-necked flask, heat to 90℃, stir at 200 r / min, and purge with high-purity nitrogen gas at a flow rate of 30 mL / min. After the temperature stabilizes at 90℃, slowly add 18 parts of 2,4-toluene diisocyanate. After the addition is complete, maintain the temperature at 95℃ for 3 hours to obtain the TPU prepolymer. S3. Add 12 parts of pretreated modified polylactic acid and 15 parts of polycaprolactone to the above TPU prepolymer, heat to 105℃, increase the stirring speed to 300 r / min, and keep the reaction at this temperature for 1.5 h to form a preliminary composite system; then add 0.5 parts of antioxidant 1010 and 4 parts of epoxidized soybean oil, keep the temperature at 105℃, and continue stirring for 40 min; then slowly add 6 parts of pretreated modified nanocellulose, increase the stirring speed to 400 r / min, and keep the temperature at 105℃ for 2 h to form a uniform and stable composite system; finally add 8 parts of 1,4-butanediol, heat to 115℃, and adjust the stirring speed to 250 r / min to carry out the chain extension reaction; continuously monitor the reaction process, and when the viscosity reaches 12000 mPa·s and remains stable for 30 min, the chain extension reaction is complete, and a high-viscosity TPU composite melt is obtained; S4. Pour the extended TPU composite melt into a mold preheated to 130°C. Place the mold on a flat vulcanizing machine for compression molding. Set the molding pressure to 20MPa and the temperature to 135°C. Hold the temperature and pressure for 40 minutes. After compression molding, turn off the heating device of the flat vulcanizing machine and allow the mold and the product to cool naturally to room temperature. After cooling, demold to obtain the composite material blank. Place the composite material blank in a 90°C vacuum drying oven and dry for 10 hours to obtain a biodegradable high-elasticity TPU composite material.
[0029] Example 3: Preparation of a biodegradable, highly elastic TPU composite material. The specific preparation steps are as follows: S1. Place polybutylene adipate diol in a vacuum drying oven at 105℃ and dry for 6 hours; place modified nanocellulose, modified polylactic acid, and polycaprolactone in a vacuum drying oven at 85℃ and dry for 10 hours respectively; place antioxidant 1010, epoxidized soybean oil, and 1,4-butanediol in a dry sealed container for later use. S2. Add 40 parts of pretreated polybutylene adipate diol to a four-necked flask, heat to 85°C, stir at 175 r / min, and purge with high-purity nitrogen gas at a flow rate of 25 mL / min. After the temperature stabilizes at 87°C, slowly add 15 parts of 2,4-toluene diisocyanate. After the addition is complete, maintain the temperature at 90°C for 2.5 h to obtain the TPU prepolymer. S3. Add 8 parts of pretreated modified polylactic acid and 11 parts of polycaprolactone to the above TPU prepolymer, heat to 100℃, increase the stirring speed to 275 r / min, and keep the reaction at this temperature for 1.2 h to form a preliminary composite system; then add 0.4 parts of antioxidant 1010 and 2 parts of epoxidized soybean oil, keep the temperature at 100℃, and continue stirring for 35 min; then slowly add 4 parts of pretreated modified nanocellulose, increase the stirring speed to 375 r / min, and keep the temperature at 100℃ for 1.7 h to form a uniform and stable composite system; finally add 5 parts of 1,4-butanediol, heat to 110℃, and adjust the stirring speed to 225 r / min to carry out the chain extension reaction; continuously monitor the reaction process, and when the viscosity reaches 10000 mPa·s and remains stable for 30 min, the chain extension reaction is complete, and a high-viscosity TPU composite melt is obtained; S4. Pour the extended TPU composite melt into a mold preheated to 125°C. Place the mold on a flat vulcanizing machine for compression molding. Set the molding pressure to 17MPa and the temperature to 130°C. Hold the temperature and pressure for 35 minutes. After compression molding, turn off the heating device of the flat vulcanizing machine and allow the mold and the product to cool naturally to room temperature. After cooling, demold to obtain the composite material blank. Place the composite material blank in an 85°C vacuum drying oven and dry for 10 hours to obtain a biodegradable high-elasticity TPU composite material.
[0030] Example 4: Preparation of modified nanocellulose. The specific preparation steps are as follows: A1. Take 10g of nanocellulose, add 450mL of deionized water, and ultrasonically disperse for 40min to obtain a nanocellulose dispersion. Place it in a three-necked flask, heat to 60℃, and stir at 200r / min. Slowly add 18mL of silane coupling agent KH-560 to the flask, and simultaneously add 12g of 15% sodium carbonate solution in 3 portions. After the addition is complete, keep the reaction at the temperature for 5h. Then add 8g of bisphenol F diglycidyl ether and continue to keep the reaction at the temperature for 3h. After the reaction is complete, adjust the pH of the system to 6.5 with 5% acetic acid solution, vacuum filter, wash the filter cake 3 times with deionized water, and dry it in a vacuum drying oven at 70℃ for 12h to obtain the first modified nanocellulose. A2. Take 8g of the first-modified nanocellulose, add 300mL of N,N-dimethylacetamide, sonicate for 30min, heat to 85℃, and stir at 250r / min; add 20g of polymethyl methacrylate microspheres to the system, stir and disperse for 20min, then slowly add 5g of hexamethylene diisocyanate, and keep the reaction at this temperature for 4h; after the reaction is complete, cool the system to room temperature, vacuum filter, soak the filter cake in acetone for 8h, then wash twice with acetone and once with deionized water, and dry in a vacuum drying oven at 75℃ for 10h to obtain the second-modified nanocellulose; A3. Take 6g of the second modified nanocellulose, add 250mL of 0.1mol / L phosphate buffer (pH=7.2), sonicate for 15min, add 10g of glucose oxidase, and stir at 4℃ for 12h. Add 6g of 25% glutaraldehyde aqueous solution to the system and stir at room temperature for 2h. Then add 1.2g of glycine and stir at 25℃ for 30min to quench the aldehyde group. After the reaction, vacuum filter the mixture and wash the filter cake with 50℃ deionized water until the filtrate is free of aldehydes when tested with 2,4-dinitrophenylhydrazine test paper. Then dry the filter cake in a 70℃ vacuum drying oven for 8h to obtain the modified nanocellulose.
[0031] Example 5: Preparation of modified nanocellulose. The specific preparation steps are as follows: A1. Take 10g of nanocellulose, add 550mL of deionized water, and ultrasonically disperse for 40min to obtain a nanocellulose dispersion. Place it in a three-necked flask, heat to 70℃, and stir at 300r / min. Slowly add 25mL of silane coupling agent KH-560 to the flask, and simultaneously add 18g of 15% sodium carbonate solution in 3 portions. After the addition is complete, keep the reaction at the temperature for 7h. Then add 12g of bisphenol F diglycidyl ether and continue to keep the reaction at the temperature for 4h. After the reaction is complete, adjust the pH of the system to 7.5 with 5% acetic acid solution, vacuum filter, wash the filter cake 3 times with deionized water, and dry it in a vacuum drying oven at 70℃ for 12h to obtain the first modified nanocellulose. A2. Take 8g of the first-modified nanocellulose, add 400mL of N,N-dimethylacetamide, ultrasonically disperse for 30min, heat to 95℃, and stir at 350r / min; add 30g of polymethyl methacrylate microspheres to the system, stir and disperse for 20min, then slowly add 8g of hexamethylene diisocyanate, and keep the reaction at the temperature for 6h; after the reaction is completed, cool the system to room temperature, vacuum filter, soak the filter cake in acetone for 12h, then wash twice with acetone and once with deionized water, and dry in a vacuum drying oven at 75℃ for 10h to obtain the second-modified nanocellulose; A3. Take 6g of the second modified nanocellulose, add 350mL of 0.1mol / L phosphate buffer (pH=7.2), sonicate for 15min, add 15g of glucose oxidase, and stir at 8℃ for 16h. Add 10g of 25% glutaraldehyde aqueous solution to the system and stir at room temperature for 3h. Then add 2.0g of glycine and stir at 25℃ for 30min to quench the aldehyde group. After the reaction, vacuum filter the mixture and wash the filter cake with 50℃ deionized water until the filtrate is free of aldehydes when tested with 2,4-dinitrophenylhydrazine test paper. Then dry the filter cake in a 70℃ vacuum drying oven for 8h to obtain the modified nanocellulose.
[0032] Example 6: Preparation of modified polylactic acid. The specific preparation steps are as follows: B1. Take 20g of polylactic acid, add 400mL of chloroform, place in a three-necked flask, heat to 45℃, stir at 150r / min until the polylactic acid is completely dissolved, add 15g of polypropylene glycol diacrylate, stir and disperse for 10min, then add 0.8g of 2,2-dimethoxy-2-phenylacetophenone, turn on ultraviolet light irradiation, wavelength 365nm, power 300W, irradiation distance 10cm, react for 3h; after the reaction is completed, pour the system into anhydrous ethanol to precipitate, let stand for 3h, then vacuum filter, wash the filter cake twice with anhydrous ethanol, place in a vacuum drying oven at 55℃ and dry for 12h to obtain the first modified polylactic acid; B2. Take 15g of the first-modified polylactic acid and add it to the feed inlet of a twin-screw extruder. Set the temperatures of each zone of the extruder as follows: Zone 1 165℃, Zone 2 175℃, Zone 3 180℃, Die head 175℃, and screw speed 110r / min to melt and plasticize it. The melt residence time is 2min. Add 12g of adipate dihydrazide and 5g of tributyl citrate at a uniform speed through the side feed port. The reaction residence time is 3min. After cooling the extrudate to room temperature with water, cut it into pellets with a pelletizer to obtain second-modified polylactic acid granules with a particle size of 2mm. B3. Take 12g of the second modified polylactic acid granules and add them to a mixer. Set the mixing temperature to 175℃ and the rotor speed to 70r / min. After melting for 5min, add 8g of polyetheramine D230 and 2g of maleic anhydride-grafted polyolefin and continue mixing for 10min. Take out the mixing product and place it on a flat vulcanizing machine to press it into sheets. Set the temperature to 180℃, the pressure to 10MPa, and the time to 3min. After cooling to room temperature, pulverize and pass it through an 80-mesh sieve to obtain modified polylactic acid.
[0033] Example 7: Preparation of modified polylactic acid. The specific preparation steps are as follows: B1. Take 20g of polylactic acid, add 500mL of chloroform, place in a three-necked flask, heat to 55℃, stir at 200r / min until the polylactic acid is completely dissolved, add 22g of polypropylene glycol diacrylate, stir and disperse for 10min, then add 1.5g of 2,2-dimethoxy-2-phenylacetophenone, turn on ultraviolet light irradiation, wavelength 365nm, power 300W, irradiation distance 15cm, react for 5h; after the reaction is completed, pour the system into anhydrous ethanol to precipitate, let stand for 4h, then vacuum filter, wash the filter cake 3 times with anhydrous ethanol, place in a 55℃ vacuum drying oven and dry for 16h to obtain the first modified polylactic acid; B2. Take 15g of the first-modified polylactic acid and add it to the feed inlet of a twin-screw extruder. Set the temperatures of each zone of the extruder as follows: Zone 1 175℃, Zone 2 185℃, Zone 3 185℃, Die head 180℃, and screw speed 130r / min to melt and plasticize it. The melt residence time is 3min. Add 18g of adipate dihydrazide and 9g of tributyl citrate at a uniform rate through the side feed port. The reaction residence time is 5min. After cooling the extrudate to room temperature with water, cut it into pellets with a pelletizer to obtain second-modified polylactic acid granules with a particle size of 3mm. B3. Take 12g of the second modified polylactic acid granules and add them to a mixer. Set the mixing temperature to 185℃ and the rotor speed to 90r / min. After melting for 8min, add 14g of polyetheramine D230 and 5g of maleic anhydride-grafted polyolefin and continue mixing for 15min. Take out the mixing product and place it on a flat vulcanizing machine to press it into sheets. The temperature is 190℃, the pressure is 15MPa, and the time is 5min. After cooling to room temperature, pulverize it and pass it through an 80-mesh sieve to obtain modified polylactic acid.
[0034] Comparative Example 1: A biodegradable and highly elastic TPU composite material was prepared. The specific preparation steps are as follows: The remaining steps remain the same, except that the modified nanocellulose prepared in Example 4 used in Example 3 is replaced with unmodified nanocellulose to prepare a biodegradable and highly elastic TPU composite material.
[0035] Comparative Example 2: A biodegradable and highly elastic TPU composite material was prepared. The specific preparation steps are as follows: The remaining steps remain the same, except that the modified polylactic acid prepared in Example 7 and used in Example 3 is replaced with unmodified polylactic acid to prepare a biodegradable and highly elastic TPU composite material.
[0036] Comparative Example 3: A biodegradable and highly elastic TPU composite material was prepared. The specific preparation steps are as follows: The remaining steps remain unchanged, except that the modified nanocellulose prepared in Example 4 used in Example 3 is replaced with unmodified nanocellulose, and the modified polylactic acid prepared in Example 7 is replaced with unmodified polylactic acid, so as to prepare a biodegradable and highly elastic TPU composite material.
[0037] Performance testing
[0038]
[0039] Performance test results show that the biodegradable high-elasticity TPU composite materials prepared in Examples 1-3 are significantly superior to those in Comparative Examples 1-3 in terms of overall performance: tensile strengths reach 26.8 MPa, 28.5 MPa, and 30.2 MPa, respectively; elongation at break is 810%-860%; elastic recovery rate is 88%-94%; and soil compost degradation rate is 62%-68% after 6 months. In contrast, Comparative Examples 1-3, which did not use modified nanocellulose, modified polylactic acid, or neither, have tensile strengths of only 17.5-21.3 MPa, elongation at break of 520%-650%, elastic recovery rate of 68%-75%, and degradation rate of 48%-55%, all of which are significantly lower. This fully demonstrates that multi-step modified nanocellulose and polylactic acid can effectively improve the compatibility, mechanical properties, elasticity, and degradability of the material.
[0040] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in the claims, all of which should fall within the protection scope of the present invention.
Claims
1. A biodegradable, highly elastic TPU composite material, characterized in that: It contains the following raw materials in parts by weight: 35-45 parts polybutylene adipate diol, 12-18 parts 2,4-toluene diisocyanate, 3-8 parts 1,4-butanediol, 2-6 parts modified nanocellulose, 5-12 parts modified polylactic acid, 8-15 parts polycaprolactone, 0.2-0.5 parts antioxidant 1010, and 1-4 parts epoxidized soybean oil.
2. The biodegradable, highly elastic TPU composite material according to claim 1, characterized in that: The polybutylene adipate diol has a number-average molecular weight of 2000-3000.
3. The biodegradable, highly elastic TPU composite material according to claim 1, characterized in that: The polycaprolactone has a number-average molecular weight of 1500-2500, a melt index of 5-12 g / 10 min at 190℃ / 2.16 kg, and a terminal hydroxyl content of ≥98%.
4. The biodegradable, highly elastic TPU composite material according to claim 1, characterized in that: The modified nanocellulose is prepared using the following specific steps: A1. Take nanocellulose, add deionized water, and ultrasonically disperse for 40 min to obtain nanocellulose dispersion. Place it in a three-necked flask, heat to 60-70℃, and stir at 200-300 r / min. Slowly add silane coupling agent KH-560 to the flask, and simultaneously add 15% sodium carbonate solution in 3 portions. After the addition is complete, keep the reaction at the temperature for 5-7 h. Then add bisphenol F diglycidyl ether and continue to keep the reaction at the temperature for 3-4 h. After the reaction is complete, adjust the pH of the system to 6.5-7.5 with 5% acetic acid solution, vacuum filter, wash the filter cake 3 times with deionized water, and dry it in a vacuum drying oven at 70℃ for 12 h to obtain the first modified nanocellulose. A2. Take the first modified nanocellulose, add N,N-dimethylacetamide, ultrasonically disperse for 30 min, heat to 85-95℃, and stir at 250-350 r / min; add polymethyl methacrylate microspheres to the system, stir and disperse for 20 min, then slowly add hexamethylene diisocyanate, and keep the reaction at the temperature for 4-6 h; after the reaction is completed, cool the system to room temperature, vacuum filter, soak the filter cake in acetone for 8-12 h, then wash twice with acetone and once with deionized water, and dry in a vacuum drying oven at 75℃ for 10 h to obtain the second modified nanocellulose; A3. Take the second modified nanocellulose, add 0.1 mol / L phosphate buffer (pH=7.2), sonicate for 15 min, add glucose oxidase, and stir for 12-16 h at 4-8℃. Add 25% glutaraldehyde aqueous solution to the system and stir for 2-3 h at room temperature. Then add glycine and stir for 30 min at 25℃ to quench the aldehyde group. After the reaction, vacuum filter the mixture and wash the filter cake with 50℃ deionized water until the filtrate is free of aldehydes when tested with 2,4-dinitrophenylhydrazine test paper. Then dry the filter cake in a 70℃ vacuum drying oven for 8 h to obtain modified nanocellulose.
5. The biodegradable, highly elastic TPU composite material according to claim 4, characterized in that: The ratio of nanocellulose, deionized water, silane coupling agent KH-560, sodium carbonate solution, and bisphenol F diglycidyl ether in A1 is 10g:450-550mL:18-25mL:12-18g:8-12g; the epoxy value of the bisphenol F diglycidyl ether is 0.55-0.60mol / 100g. The ratio of the first modified nanocellulose, N,N-dimethylacetamide, polymethyl methacrylate, and hexamethylene diisocyanate in A2 is 8g:300-400mL:20-30g:5-8g; the polymethyl methacrylate microspheres have a particle size of 200-500nm. The ratio of the amount of the second modified nanocellulose, phosphate buffer, glucose oxidase, glutaraldehyde aqueous solution and glycine in A3 is 6g: 250-350mL: 10-15g: 6-10g: 1.2-2.0g.
6. The biodegradable, highly elastic TPU composite material according to claim 1, characterized in that: The modified polylactic acid is prepared using the following specific steps: B1. Take polylactic acid, add chloroform, place in a three-necked flask, heat to 45-55℃, stir at 150-200 r / min until polylactic acid is completely dissolved, add polypropylene glycol diacrylate, stir and disperse for 10 min, then add 2,2-dimethoxy-2-phenylacetophenone, turn on ultraviolet light irradiation, wavelength 365nm, power 300W, irradiation distance 10-15cm, react for 3-5 h; after the reaction is completed, pour the system into anhydrous ethanol to precipitate, let stand for 3-4 h, then vacuum filter, wash the filter cake 2-3 times with anhydrous ethanol, place in a 55℃ vacuum drying oven and dry for 12-16 h to obtain the first modified polylactic acid; B2. Take the first-modified polylactic acid and add it to the feed inlet of a twin-screw extruder. Set the temperatures of each zone of the extruder as follows: Zone 1 165-175℃, Zone 2 175-185℃, Zone 3 180-185℃, Die head 175-180℃, and screw speed 110-130 r / min to melt and plasticize it. The melt residence time is 2-3 min. Add adipate dihydrazide and tributyl citrate at a uniform rate through the side feed port. The reaction residence time is 3-5 min. After cooling the extrudate to room temperature with water, granulate it through a pelletizer to obtain second-modified polylactic acid granules with a particle size of 2-3 mm. B3. Take the second batch of modified polylactic acid granules and add them to a mixer. Set the mixing temperature to 175-185℃ and the rotor speed to 70-90 r / min. After melting for 5-8 min, add polyetheramine D230 and maleic anhydride-grafted polyolefin and continue mixing for 10-15 min. Take out the mixing product and place it on a flat vulcanizing machine for pressing into sheets. Set the temperature to 180-190℃, the pressure to 10-15 MPa, and the time to 3-5 min. After cooling to room temperature, pulverize and pass through an 80-mesh sieve to obtain modified polylactic acid.
7. The biodegradable, highly elastic TPU composite material according to claim 6, characterized in that: The ratio of polylactic acid, chloroform, polypropylene glycol diacrylate, and 2,2-dimethoxy-2-phenylacetophenone in B1 is 20g: 400-500mL: 15-22g: 0.8-1.5g. The ratio of the first modified polylactic acid, adipate dihydrazide, and tributyl citrate in B2 is 15g:12-18g:5-9g; The ratio of the second modified polylactic acid particles, polyetheramine D230, and maleic anhydride grafted polyolefin in B3 is 12g:8-14g:2-5g.
8. A method for preparing a biodegradable, highly elastic TPU composite material, characterized in that: Specifically, it includes the following steps: S1. Place polybutylene adipate diol in a vacuum drying oven at 100-110℃ and dry for 6 hours; place modified nanocellulose, modified polylactic acid, and polycaprolactone in a vacuum drying oven at 80-90℃ and dry for 10 hours respectively; place antioxidant 1010, epoxidized soybean oil, and 1,4-butanediol in a dry, sealed container for later use. S2. Add 35-45 parts of pretreated polybutylene adipate diol to a four-necked flask, heat to 80-90℃, stir at 150-200 r / min, and purge with high-purity nitrogen gas at a flow rate of 20-30 mL / min. After the temperature stabilizes at 85-90℃, slowly add 12-18 parts of 2,4-toluene diisocyanate. After the addition is complete, maintain the temperature at 85-95℃ for 2-3 hours to obtain the TPU prepolymer. S3. Add 5-12 parts of pretreated modified polylactic acid and 8-15 parts of polycaprolactone to the above TPU prepolymer, heat to 95-105℃, increase the stirring speed to 250-300 r / min, and maintain the temperature for 1-1.5 h to form a preliminary composite system; then add 0.2-0.5 parts of antioxidant 1010 and 1-4 parts of epoxidized soybean oil, maintain the temperature at 95-105℃, and continue stirring for 30-40 min; then slowly add 2-6 parts of pretreated modified nanocellulose. Increase the stirring speed to 350-400 r / min, maintain the temperature at 95-105℃ for 1.5-2 h to form a uniform and stable composite system; finally, add 3-8 parts of 1,4-butanediol, raise the temperature to 105-115℃, and adjust the stirring speed to 200-250 r / min to carry out the chain extension reaction; continuously monitor the reaction process, and when the viscosity reaches 8000-12000 mPa·s and remains stable for 30 min, the chain extension reaction is complete, and a high-viscosity TPU composite melt is obtained; S4. Pour the extended TPU composite melt into a mold preheated to 120-130℃. Place the mold on a flat vulcanizing machine for compression molding. Set the molding pressure to 15-20MPa and the temperature to 125-135℃, and maintain the temperature and pressure for 30-40 minutes. After compression molding, turn off the heating device of the flat vulcanizing machine and allow the mold and the product to cool naturally to room temperature. After cooling, demold to obtain the composite material blank. Place the composite material blank in a vacuum drying oven at 80-90℃ and dry for 10 hours to obtain a biodegradable high-elasticity TPU composite material.
Citation Information
Patent Citations
Poly(butylene adipate / terephthalate) / nano-cellulose degradable composite material and preparation method thereof
CN104672825A
Thermoplastic polyurethane elastomer material for degradable medical-grade film and preparation method thereof
CN110922559A
High bio-based TPU composite material and preparation method thereof
CN117866414A
Degradable nanocellulose composite packaging material and preparation method thereof
CN118725531A
Environment-friendly aliphatic TPU (thermoplastic polyurethane) elastic plastic
CN119552336A